ABDOMINAL TUBERCULOSIS WITH DIFFERENT MANAGEMENT MODALITIES IN SMT SHARDABEN GENERAL HOSPITAL SARASPUR AHMEDABAD (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background: Tuberculosis is a major health hazard in India. Because of its diverse manifestation ,difficult diagnosis, widespread complication ,prolonged morbidity and increased mortality the study of this disease becomes even more important .The objectives of the study were to study age and sex distribution of abdominal tuberculosis ,to study the association of abdominal tuberculosis with pulmonary tuberculosis ,various clinical presentation of abdominal tuberculosis ,to study surgical management of abdominal tuberculosis. Methods: The study was carried out in 30 patients of abdominal tuberculosis of different age group and sex admitted in department of surgery , Smt SCL hospital , Saraspur , Ahmedabad during period of April 2018 to march 2019.This is the prospective study in which patients are present with acute abdomen like intestinal obstruction ,peritonitis ,RIF lump taken ,further investigated and laparotomies were performed and AKT started after proven by biopsy reports. RESULTS: In my study most common age group affected is between 2nd to 4th decade and gender wise male are more affected then female., Most common symptom of presentation is abdominal pain mostly at RIF and periumbilical region associated with anorexia and vomiting and abdominal distension .Out of 30 patients 19 patients had pulmonary tuberculosis and patient had completed course of AKT. CONCLUSION: In all 30 patients present as acute abdomen. Patients present with peritonitis were explored in emergency and other patients initially conservatively managed after all radiological investigations on patients were explored ,Biopsy reports were collected and after confirmation of tuberculosis AKT (ISONIAZID,RIFAMPICIN,PYRAZINEMIDE,ETHAMBUTOL and STRPTOMYCIN,LEVOFLOXACIN.) started .Good clinic pathological workup in patients of abdominal tuberculosis results in earlier diagnosis and timely management of this curable disease.
Keywords: tuberculosis; Anti Koch’s treatment; surgery